Economic development of tropical agriculture: theory, policy, strategy, and organization. - McPherson, W. W. (Gainesville University of Florida Press, 1968)
This volume comprises fifteen papers presented in a series of seminars held at the University of Florida, Gainesville, by a group of internationally recognized experts-a veritable "Who's Who" of specialists in tropical agriculture.
lje 14/06/17
Loans
Keywords: Agriculture -- Economic aspects; Tropics; Developing countries